Scrutinizing the Application of Saline Endophyte to Enhance Salt Tolerance in Rice and Maize Plants - Siddiqui, Zamin Shaheed; Wei, Xiangying; Umar, Muhammad; Abideen, Zainul; Zulfiqar, Faisal; Chen, Jianjun; Hanif, Asma; Dawar, Shahnaz; Dias, Daniel Anthony; Yasmeen, Roomana (Frontiers in Plant Science, 2022)
The present study aimed to witness the plant-microbe interaction associated with salt tolerance in crops. We isolated the endophytic microbe from the root zone of halophytic grass. Later, the salt tolerance of the endophyte was tested in the saline medium and was identified using nucleotide sequencing (GenBank under the accession numbers: SUB9030920 AH1_AHK_ITS1 MW570850: SUB9030920 AH1_AHK_ITS4 MW570851). Rice and maize seeds were coated with identified endophyte Aspergillus terreus and were sown in separate plastic pots. Later twenty-one-day-old seedlings were subjected to three NaCl concentrations, including 50, 00, and 150-mM salt stress. Under saline conditions, A. terreus showed a substantial increase in growth, biomass, relative water content, oxidative balance, and photochemical efficiency (PSII) of both rice and corn plants. The data reflected the stimulation of Gibberellic acid and up-regulation of photosynthesis and antioxidant defense cascade. The data also depict the downregulation of oxidative damage markers MDA, H2O2 in rice and Maize plants. Conclusively, salt-tolerant endophytic fungus A. terreus explicitly displayed the positive plant-microbe interaction by developing salt tolerance in rice and Maize plants. Salt tolerance by endophytic fungus coincides with the enhanced GA concentration, which illustrated the stimulated physiological mechanism and gene in response to cope with the extreme environmental crisis, resulting in improved crop productivity.